THE ROLE OF THE “CHILD/BOLA” CONCEPT IN ENHANCING ENGLISH LANGUAGE TEACHING FOR UZBEK LEARNERS: A CULTURAL AND PROGMATIC PERSPECTIVE - Turgunova Buxalicha (Uz Conferences, 2025)
This article delves into the significance of the "Child/Bola" concept in English language teaching (ELT), examining its cultural and pragmatic relevance. By analyzing the linguistic and cultural nuances of "child" in English and "bola" in Uzbek, the study highlights how integrating this concept can enhance linguistic competence, cultural awareness, and intercultural communication skills. The paper also provides practical strategies for incorporating this concept into teaching methodologies, emphasizing its role in contextualizing language learning and fostering meaningful engagement.